Bridging culture and math: The Javanese calendar as an educational tool - Utami, Niken Wahyu; Putri, Alfianti Kusuma (Universitas Papua, 2024)
The Javanese calendar is familiar to Javanese people. The calendar has a contextual side that has many opportunities to be used in learning mathematics. However, the utilization of the Javanese calendar has not been comprehensively explored. This research reveals the mathematical underpinnings of the Javanese calendar and how these can be leveraged to design effective educational strategies. The research method we used was qualitative, through a review of documents containing references to the Javanese calendar and school mathematics literature. The results showed that the Javanese calendar has mathematical value for learning mathematics regarding number recognition and addition, multiples of numbers, and Lowest Common Multiple (LCM). In addition, number sets, data presentation, relations, and functions. This research implies that the Javanese calendar can be used as a context for learning mathematics in schools.